Drivhusmodellen i teori och praktik : ett verksamhetsintegrerat forsknings- och utvecklingsarbete för integration av utbildning, forskning och samverkan vid Luleå tekniska universitet - Andersson, Mikael (Luleå, 2003)
This thesis concerns the development of a model for integration of education, research and cooperation intended for university use. The thesis builds on a research and development work integrated in the daily educational activity of the university. The model; the Green-house model combines experience-based learning with theory-based learning dialectically. The model and it's correspondent activities and practice is developed at the Luleå Technical University inside the four green-houses started in the Arena for Innovative Technology and Business. The purpose of the green-house is to introduce a cross-functional knowledge- building which is characterised by multidisciplinarity, the participation of different professions, the cooperation with actors from the surrounding society, that all actors are active and a cooperation that is based on equality between actors. Students and researchers participate in a green-house activity through a role/function related to a profession. In this activity situations occur that generates the need of action. If this need can be satisfied through re- creational actions these can be made the subject of reflection. If not the situation has generated a problem. In this case the acting unit, a person or a group must use their imagination (and creativity) to create innovative action. The starting point of the action can be found in the following areas of knowledge: the activity, the situation (needs, related problems and phenomena) and the actors function (role and/or group). The knowledge can be viewed out of the following aspects of knowledge: declarative and familiar knowledge, judgment and ability. These aspects can be discerned in connection with all these areas of knowledge. Put together this describes the learning process in the Green-house model. The long-term aim of the integration of experience-based learning with theory-based learning and the applied learning-process according to the green-house model is to enhance the possibility for development-oriented learning (which is ...